SUITABILITY OF BI-VACANCY TRAP FOR TL EMISSION IN KCl - Pandey, Ruchi; Pandey, Shankar Datt; Kumar, Sumit; Kumar, Rajendra (Malaysian Journal of Science, 2021)
In KCl crystals, the 2s energy level of F-center within an anion-cation vacancy pair has been proposed as a suitable trap for thermoluminescence (TL) emission. It is further seen that the 2s – level of F-center situated in cation – anion vacancy pair has large trap depth. The observed trap depth of F-center is explainable on the basis of Herman and Barnett model, modified presently and supports bi-vacancy configuration for traps in KCl lattice.